A taxonomic revision of the Patagonian species of the Dasyhelea mutabilis species group with a phylogenetic analysis of New World species (Diptera: Ceratopogonidae) - Díaz, Florentina (2014)
We provide a taxonomic revision of the Dasyhelea mutabilis species group inhabiting Patagonia, including diagnoses and identification key for both sexes of all species, descriptions and illustrations of seven new and three previously described species, and a discussion of phylogenetic relationships for each species. In addition, a cladistic analysis of the Neotropical and Nearctic species of the mutabilis group was performed using TNT version 1.1. It suggests that this group is not monophyletic, and this and other results are discussed within a phylogenetic framework.